2020
DOI: 10.1108/ajb-03-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bank and credit union growth around the financial crisis

Abstract: PurposeThe purpose of this research is to examine the growth rates of commercial banks and credit unions around the financial crisis and recovery. Credit unions are analyzed as a group and by field of membership. Specifically, this research analyzes the growth rates of assets, deposits, and loans.Design/methodology/approachThis research employs univariate tests of differences to examine the median growth rates for commercial banks and credit unions. Unbalanced pool regressions analyze growth rates during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…Banks, especially those whose regulatory ratings were downgraded during this period, saw a sharp decline in loans to small and medium-sized enterprises [ 9 ]. With the financial crisis affecting the whole economic development, the American public’s trust in banks had decreased, the function of banks to absorb and mobilize savings had been weakened, and a large amount of savings had been deposited in credit cooperatives [ 10 ]. It is generally believed that the banking industry triggered the financial crisis, but there is still a gap in the understanding of the causal relationship between banking and economic growth before and after the crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Banks, especially those whose regulatory ratings were downgraded during this period, saw a sharp decline in loans to small and medium-sized enterprises [ 9 ]. With the financial crisis affecting the whole economic development, the American public’s trust in banks had decreased, the function of banks to absorb and mobilize savings had been weakened, and a large amount of savings had been deposited in credit cooperatives [ 10 ]. It is generally believed that the banking industry triggered the financial crisis, but there is still a gap in the understanding of the causal relationship between banking and economic growth before and after the crisis.…”
Section: Introductionmentioning
confidence: 99%
“…We do not have sufficient evidence to assess the relative resilience of the community-based lending model in the face of economic downturns, which is a key question in the academic literature (Lu and Swisher, 2020; Coen et al, 2019). The long-term impact of COVID-19 on affordable credit sector and access to credit for financially excluded consumers is still uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Credit unions are not only less likely to experience steep declines in lending during crises, but there is also evidence from the US suggesting that credit unions provide additional liquidity when banks are reducing credit supply. Lu and Swisher (2020) found that US credit union lending grew at a faster rate than bank lending during and following the global financial crisis of 2007. A study by Walker (2016), which examined bank and credit union business lending for 2010-14, concluded that credit unions increased their share of business lending following the financial and economic crisis of 2007. Business loans from credit unions increased by 39.2%, while assets increased by 22.7%.…”
Section: The Impact Of Covid-19 On the Community Finance Sectormentioning
confidence: 99%
“…The role of banking in a country is so vital that management must pay attention to banking performance. Banks have become one of the fastest growing industries and the high and optimistic growth rate of banking assets occurs from year to year (Lu and Swisher, 2020). The ability of banks to carry out their role in determining the economy depends on efficient and effective bank management.…”
Section: Introductionmentioning
confidence: 99%